Análise dos pontos de convergência entre tecnologias da Indústria 4.0 e práticas Lean Seis Sigma em processos de manufatura: um estudo multicasos - Sordan, Juliano Endrigo (2020)
The literature on operational excellence recognizes that the Lean Six Sigma approach can promote the continuous improvement of business processes in terms of quality, cost, and speed. On the other hand, the recent paradigm of Industry 4.0 has been creating challenges and opportunities regarding the adoption of digital technologies in manufacturing processes and connecting the physical world to the virtual world through Cyber-physical Systems. Although the literature presents studies that integrate practices isolated from Lean Manufacturing or Six Sigma approaches with specific technologies from Industry 4.0, the systemic integration between these elements still represents an important theoretical gap. This thesis aims to analyze the points of convergence between technologies of industry 4.0 and Lean Six Sigma practices in manufacturing processes. To this end, a systematic literature review was carried out, giving rise to a conceptual research analysis structure that brings together thirteen points of convergence. This structure covers five categories of analysis directly related to research questions: points of convergence, information technology requirements, automation requirements, competence requirements, and results. In order to validate this structure, a multi-case study was conducted involving two companies in the automotive sector, with experience in Lean Six Sigma practices, whose manufacturing processes demonstrated evidence of conversion to the Industry 4.0 model. The research approach combined qualitative and quantitative techniques and made it possible to measure the perceptions of interviewees, as well as the analysis of internal documents and on-site observations. The empirical evidence highlighted the most expressive points of contact in these organizations and allowed the establishment of theoretical propositions. As a practical contribution, this study may assist in development of digital transformation strategies within the scope of operational excellence initiatives.